PENGARUH PENERAPAN MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 110 PEKANBARU (STUDI EKSPERIMEN QUASI) - Sandra Syamriona; Hendri Marhadi; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is based on the low learning outcomes of students especially on subjects IPS. This happens because at the time of the learning process students are less interested with the material being taught because the teacher is still using lecture methods and less conducive class circumstances, less lighting, slightly narrow and less well organized that makes students become bored and unmotivated to learn. The application of quantum teaching model is expected to be influential in improving students' IPS learning outcomes. This research is a research with quasi experimental method with nonequivalent control group design. The purpose of this study is to determine the effect of the application of quantum teaching model to the learning outcomes of IPS students of class III State Elementary School 110 Pekanbaru in the experimental class and to know the difference in learning outcomes of IPS students of third grade students of Elementary School 110 Pekanbaru between experimental class and control class. This research was conducted in SD Negeri 110 Pekanbaru with class IIIA as control class treated with ordinary learning and class IIIB as experimental class treated by applying quantum teaching model. The result of the research shows that there is influence of the application of quantum teaching model to IPS learning result and there are difference of IPS learning achievement between experimental class and control class. In the experimental class there was an increase in IPS learning outcomes from the pretest average of 61.91 to 75.58 in the posttest test with an average gain of 0.38 medium category. While the control class had an increase of 62.05 on pretest to 67.64 in the final test (postest) with an average gain of 0.12 low category. In this research, it is known that there is influence of the application of quantum teaching model is strong enough to the learning result of IPS of third grade students of State Elementary School 110 Pekanbaru in experiment class with coefficient of determination 0,53. The quantum teaching model influences the IPS learning result by 53.29% while the other 46.71% is influenced by other factors, it can come from inside the students (intern) and from outside the students themselves (extern).Key Word : Quantum Teaching Model, IPS Learning Result